Municipal management as the basis of public management of sustainable infrastructure of communities - Postupna , Olena (Pressing Problems of Public Administration, 2025)
The article is devoted to the theoretical substantiation of the role of municipal management as a key tool in the public administration system aimed at ensuring the sustainability and resilience of the infrastructure of territorial communities in the context of decentralization and modern challenges.It is established that the inefficiency of management is due to the dominance of a reactive approach over strategic planning, which leads to critical depreciation of fixed assets and financial instability. To overcome these dysfunctions, the need to transition to proactive, innovative management is substantiated.The central result of the study is the development of a partnership model “Governance Triangle”, which involves the synergy of public administration bodies, the private sector and civil society. It is determined that this model provides diversification of financing (through public-private partnership mechanisms) a]nd increases the legitimacy of management decisions. At the same time, key threats to the model are identified, including the risk of “capture” by private business and the institutional immaturity of control mechanisms.A set of practical recommendations is proposed, including the implementation of smart technologies (GIS) for asset monitoring, the development of human capital of facilitator managers, and the integration of an early warning system, which are necessary to ensure sustainable and innovative infrastructural development of communities..